Connections and Disconnections in the Armenian Transnation: the Case of Armenian Americans and Armenia - Anouche Der Sarkissian (Revue LISA)
The Armenian dispersion is often studied as a textbook diaspora, with a common origin, collective memory, shared interests, and a sense of co-responsibility. Among the different components of the Armenian “transnation,” Armenian Americans occupy a unique and influential position. The long history of Armenian migration to North America has given rise to a visible ethno-cultural community that has been at the forefront of multifaceted efforts to preserve the ancestral culture, assist Armenia, and campaign for certain causes, with recognition of the Armenian Genocide of 1915 being the most emblematic. However, despite this “special relationship”, for more than a century, the connection between Armenian Americans and the Republic of Armenia has been complex, consisting of cooperation, dependence, disagreements, contested leadership and thwarted dreams. In addition, since the 1960s the continual influx to the US of Armenian migrants hailing from different countries has contributed to an extremely composite stock of Armenian Americans, one that hardly conforms to the traditional definitions of a diaspora. Such internal fragmentation translates into heterogeneous transnational practices and multiple forms of engagement with Armenia. This article uses the example of Armenian Americans to show that the relationship between a diaspora and its homeland does not necessarily run along a smooth and even path. The ebb and flow of history changes the nation-state and its exile community and eventually impacts the ties they maintain.